HUBUNGAN BUDAYA SEKOLAH DENGAN PRESTASI AKADEMIK SISWA KELAS V SD INPRES KASSI-KASSI - Nurul Safika; Laubeka, Nurhalisa; Rahmawati, Indi; Muslimah, Haera; Novelia, Natasya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between school culture and academic achievement of fifth grade students at SD Inpres Kassi-Kassi. The research used a quantitative approach with a survey method. The sample consisted of all fifth grade students, totaling 21 respondents with saturated sampling technique. The research instruments were a school culture questionnaire with 24 Likert scale statements and documentation of student report card scores. Data analysis techniques used validity tests, reliability tests, normality tests, and simple linear regression with JASP software. The results showed that there was no significant relationship between school culture and students' academic achievement with a significance value of 0.218 greater than 0.05. The coefficient of determination value of 0.079 or 7.9 percent indicates that school culture contributes 7.9 percent to students' academic achievement, while 92.1 percent is influenced by other factors. The regression equation obtained is Y = 92.62 – 0.054 X.